FIGUR KEPEMIMPINAN MEMEDIASI PENGARUH KUALITAS PELAYANAN ADMINISTRASI TERHADAP KEPUASAN MASYARAKAT (Studi Masyarakat Yang Mencari Pelayanan di Kantor Desa Kabupaten Sragen) - Aris Tri Haryanto; Septiana Novita Dewi (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
The purpose of this study is that this study aims to determine and analyze the influence of leadership figures mediating the influence of the quality of administrative services on community satisfaction in the Village Office in Sragen Regency. The location of this research is the Village Office in Sragen Regency. While the object of research is the community who use the administration service of the Village Office in Sragen Regency. The population in this study were all people who sought Village Office services in Sragen Regency in January 2020 as many as 1300 people. Researchers took 10% of the population as a sample, ie 130 people who use the services of the Village Office in Sragen Regency. The sampling technique uses convenience or accidental sampling, namely sampling that consists of individuals who are easily found and designed to see the character of the population easily. Hypothesis test results include the quality of administrative services and a significant positive effect on the leadership of the Village Office in Sragen Regency. The quality of administrative services has a positive and significant effect on community satisfaction in the Village Office in Sragen Regency. Leadership has a positive and significant effect on community satisfaction in the Village Office in Sragen Regency. Simultaneous test results (F test) can be concluded together that the independent variables have a significant effect on community satisfaction in the Village Office in Sragen Regency. The results of the total R2 value of 0.506 can be interpreted as variations in community satisfaction of the Village Office in Sragen Regency explained by the variable quality of administrative services, and leadership as an intervening variable of 50.6% and the remaining 49.4% explained by other variables outside the research model.